CLUSTER SAMPLING FOR DETERMINATION OF IMMUNIZATION COVERAGE: A LIMITATION - K. Nasseri; K. Mohammad; M. Khoshgam (Tehran University of Medical Sciences, 1989)
Evidence provided from studies in Iran points to a possible bias in application of the standard EPI cluster sampling procedure, When carried out in populations with highly variant birth rates, tends to over-represent the low birth rate, i.e. higher socio-economic, strata, and if the entity under study shows significant socio-economic gradient, then the estimates arrived at by this method might be highly biased. Some alternatives have been mentioned.